Monitoring efficiency and productivity of promoters in wind energy sector - Vaz, Clara B (2014)
A DEA framework is proposed to explore the differences in performance of a set of wind farms, which involves two main promoters in the Portuguese wind energy sector. The study investigates the efficiency of the promoters in maximizing the energy produced from the physical resources and the wind velocity available in each farm. The overall performance of the two promoters is analyzed by comparing their differences in terms of the efficiency spread and productivity between their best-practice frontiers. Results may be used to support decision makers in the establishment of regulation policies.